2008
DOI: 10.1007/s00203-008-0359-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of nitrogen-fixing bacteria in mangrove sediments assessed by PCR–denaturing gradient gel electrophoresis

Abstract: Culture-independent PCR-denaturing gradient gel electrophoresis (DGGE) was employed to assess the composition of diazotroph species from the sediments of three mangrove ecosystem sites in Sanya, Hainan Island, China. A strategy of removing humic acids prior to DNA extraction was conducted, then total community DNA was extracted using the soil DNA kit successfully for nifH PCR amplification, which simplified the current procedure and resulted in good DGGE profiles. The results revealed a novel nitrogen-fixing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 30 publications
3
43
1
2
Order By: Relevance
“…The DGGE fingerprint results for the surface waters and bottom waters communities were analyzed according to the method prescribed by Zhang et al [26]. The band positions and intensities were both considered.…”
Section: Resultsmentioning
confidence: 99%
“…The DGGE fingerprint results for the surface waters and bottom waters communities were analyzed according to the method prescribed by Zhang et al [26]. The band positions and intensities were both considered.…”
Section: Resultsmentioning
confidence: 99%
“…That may cause the detection of low microbial diversity in our DGGE profile (Amann et al 1995). Bacterial community structure can significantly be influenced by the environmental variables, and environmental heterogeneity can drive a taxa-area relationship of bacteria (HornerDevine et al 2004;Zhang et al 2008;Hong et al 2011;Cao et al 2012). CCA has been proven to be sensitive in detecting the relationships between microbial community composition and environmental variables (Iwamoto et al 2000;Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial community structure can significantly be influenced by the environmental variables, and environmental heterogeneity can drive a taxa-area relationship of bacteria (HornerDevine et al 2004;Zhang et al 2008;Hong et al 2011;Cao et al 2012). CCA has been proven to be sensitive in detecting the relationships between microbial community composition and environmental variables (Iwamoto et al 2000;Zhang et al 2008). Using the method of CCA, Cao et al (2012) reported that water depth and temperature were major factors shaping the community structure of ammonia-oxidizing β-Proteobacteria from the PRD to the South China Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…although a considerable amount is known about how culturable bacteria respond to environmental variables in mangrove ecosystems (Takizaqa et al, 1993;Wu 1993;Wang and hong 2005), little is known about how environmental variables influence the structure of mangrove sediment bacterial communities in situ. in this study, CCa was employed to explore how the changes in microbial community composition varied with environmental conditions, which has been proven to be sensitive in detecting the relationship between bacterial community composition and environmental parameters (iwamoto et al, 2000;Mouser et al, 2005;Jiang et al, 2007;Zhang et al, 2008). The previous studies reported that the cultivable bacteria composition has high similarity between mangrove soils collected from different mangrove areas (shome et al, 1995).…”
Section: Microbial Community Composition In Relation To Environmentalmentioning
confidence: 99%